2006
DOI: 10.1007/s00424-006-0119-9
|View full text |Cite
|
Sign up to set email alerts
|

Contractile effects of adenosine, coronary flow and perfusion pressure in murine myocardium

Abstract: There is mixed evidence adenosine receptors (ARs) may enhance myocardial contractility, although this remains contentious. We assessed inotropic actions of adenosine (50 muM) and selective AR activation with 100 nM N (6)-cyclohexyladenosine (CHA; A(1)AR agonist), 25 nM 2-[p-(2-carboxyethyl) phenethylamino]-5'-N-ethylcarboxamidoadenosine (CGS-21680; A(2A)AR agonist) and 100 nM 2-chloro-N (6)-(3-iodobenzyl)-adenosine-5'-N-methyluronamide (Cl-IB-MECA; A(3)AR agonist) in mouse hearts perfused at constant pressure,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
4
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 51 publications
2
4
0
Order By: Relevance
“…CF increased by 50%, but cardiac function did not change with increasing concentrations of the A 2a AR agonist (up to 1 M). These results are consistent with our previous reports as well as those of others (13,16,19,31) showing that A 2a AR stimulation does not alter cardiac function in isolated perfused rat hearts or isolated cardiac myocytes. In contrast, it has been reported that the A 2a AR agonist CGS-21680 (100 nM) increased LV developed pressure in isolated mouse hearts by ϳ80% (20).…”
Section: Resultssupporting
confidence: 96%
See 3 more Smart Citations
“…CF increased by 50%, but cardiac function did not change with increasing concentrations of the A 2a AR agonist (up to 1 M). These results are consistent with our previous reports as well as those of others (13,16,19,31) showing that A 2a AR stimulation does not alter cardiac function in isolated perfused rat hearts or isolated cardiac myocytes. In contrast, it has been reported that the A 2a AR agonist CGS-21680 (100 nM) increased LV developed pressure in isolated mouse hearts by ϳ80% (20).…”
Section: Resultssupporting
confidence: 96%
“…Additional studies from our laboratory (14,16) have indicated that A 2a AR stimulation has no effects on contractility in isolated rat hearts and intact porcine myocardium. Our findings are consistent with those of a study by Headrick et al (31) in which it was also shown that A 2a AR activation has no contractile effects in isolated mouse hearts. In contrast, other reports (6,8,20,30,33) have indicated that A 2a AR stimulation increases contractility in isolated rat and mouse hearts and in isolated rat cardiomyocytes.…”
supporting
confidence: 96%
See 2 more Smart Citations
“…Cardiac contraction is achieved through an increase in intracellular Ca 2+ levels and protein kinase A and protein kinase C pathways [ 37 ]. There is, however, controversy over the ability of the adenosine A 2A receptor to have a positive inotropic effect due to a number of studies revealing otherwise, such as Willems and Headrick [ 39 ], who reported that the adenosine A 2A receptor caused no contractile effects in mouse hearts. Reports of the selective the adenosine A 2A receptor agonist, 2-[p-(2-carboxyethyl)-phenethylamino]-5'-N-ethylcarboxamido adenosine (CGS-21680) causing increased LVDP and coronary flow were suggested to be instead due to the Gregg phenomenon in which increased flow increases ventricular function [ 40 ].…”
Section: Discussionmentioning
confidence: 99%